IMPLEMENTASI PEMROGRAMAN TRAINER MIKROKONTROLER ARDUINO SEBAGAI MEDIA PRAKTIKUM MIKROKONTROLER - Dzulfikhar, Bahar; -, Darwinto (Jurnal Mahasiswa Terapan, 2025)
Microcontroller practicum is an essential part of the learning process in electrical engineering and informatics, especially in understanding embedded system operations. This study aims to implement programming using an Arduino microcontroller trainer as an effective and practical learning tool for microcontroller practicum. The trainer used is a ready-to-use device equipped with various modules such as digital input-output, motor driver, and I2C. The research method includes functional testing of each module, program implementation using Arduino IDE, and of the trainer's effectiveness in supporting the learning process. Test results indicate that all modules function properly and support various basic microcontroller experiments. The implementation of this trainer has proven to enhance student interactivity and comprehension of programming and control logic. Through a hands-on learning approach, the Arduino trainer offers a practical, safe, and efficient solution for microcontroller system education.